Does Brazilian allowance for corporate equity reduce the debt bias? Evidences of rebound effect and ownership-induced ACE clientele - Portal, M. T.; Laureano, L. (Research in International Business and Finance, 2017)
We analyse if the Brazilian Allowance for Corporate Equity (ACE-type system) reduces the debt tax bias. Specifically, we study if the continuous treatment effect of interest on equity negatively affects the level of financial leverage. We find that the tax policy implemented is similar to the deductible cash dividends and not to an ACE. The empirical implication is that the interest on equity treatment increases the debt tax bias, producing a rebound effect to what is expected for this policy on the risk-taking behaviour and corporate capital structure. This rebound effect is homogeneous in firms with different financial constraints status. There are evidences that shareholders influence the cash distribution policy, adjusting the later to their own tax preferences. Therefore, there may be an “ACE clientele effect” induced by heterogeneity in tax preferences among shareholders.